GAMBARAN IMPLIMENTASI AKREDITASI PUSKESMAS DI KABUPATEN/KOTA PROVINSI SUMATERA UTARA TAHUN 2016 - Susilawati Susilawati, SKM., M.Kes (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2017)
ABSTRACT Public Health Centers known as Puskesmas are first-rate health facilities (FKTP) that are responsible for public health in their work areas in one or more subdistrict areas. In the Regulation of the Minister of Health No. 75 of 2014 on Public Health Center stated that the Puskesmas is the Regional Technical Implementation Unit (UPTD) of Regency / City Health Office. In the effort to improve the quality of Puskesmas service must be accredited periodically at least 3 (three) years. (Permenkes 75 year 2014), and target of health care performance indicator target of Ministry of Health RI that is number of sub-districts having at least 1 Puskesmas certified Accreditation. To support the Accreditation Implementation Process in Puskesmas related Stakeholder roles such as District / Municipal Health Office, it is very important in the preparation stage of Puskesmas Accreditation from the initial stage until post-survey mentoring. Some things that must be prepared in the area of implementation of Puskesmas Accreditation are: Puskesmas facilities and infrastructure, Budgeting of Regency / Municipal Budget or Non-Physical DAK, SPO Preparation, Implementation Team of Puskesmas Accreditation and Accreditation Accreditation Team of Regency / City. In addition, the Puskesmas through the Implementing Team of Accreditation prepares the process of basic health services to Puskesmas Management. From the Roadmap of the Regency / City which proposed the Accreditation of Public Health Centers of 2016 amounting to 55 Puskesmas, which have received Accreditation status in 2016 there are 20 Puskesmas that meet the criteria of assessment and stages for the Accreditation Survey, which is still 28% newly accredited from the amount 571 Puskesmas. Key Word: Public health Center, acreditation